Preliminary Structure-Activity Relationships and Biological Evaluation of Novel Antitubercular Indolecarboxamide Derivatives Against Drug-Susceptible and Drug-Resistant Mycobacterium tuberculosis Strains - Onajole, O.; Pieroni, M.; Tipparaju, S.; Lun, S.; Stec, J.; Chen, G.; Gunosewoyo, Hendra; Guo, H.; Ammerman, N.; Bishai, W.; Kozikowski, A. (American Chemical Society, 2013)
Tuberculosis (TB) remains one of the leading causes of mortality and morbidity worldwide, with approximately one-third of the world’s population infected with latent TB. This is further aggravated by HIV coinfection and the emergence of multidrug- and extensively drug-resistant (MDR and XDR, respectively) TB; hence the quest for highly effective antitubercular drugs with novel modes of action is imperative. We report herein the discovery of an indole-2-carboxamide analogue, 3, as a highly potent antitubercular agent, and the subsequent chemical modifications aimed at establishing a preliminary body of structure–activity relationships (SARs). These efforts led to the identification of three molecules (12–14) possessing an exceptional activity in the low nanomolar range against actively replicating Mycobacterium tuberculosis, with minimum inhibitory concentration (MIC) values lower than those of the most prominent antitubercular agents currently in use. These compounds were also devoid of apparent toxicity to Vero cells. Importantly, compound 12 was found to be active against the tested XDR-TB strains and orally active in the serum inhibition titration assay.